The Safety and Effectiveness of Intravenous Contrast-Enhanced Sonography in Chinese Children—A Single Center and Prospective Study in China - Mao, Muyi; Xia, Bei; Chen, Weiling; Gao, Xiaojie; Yang, Jun; Li, Shoulin; Wang, Bin; Mai, Huirong; Liu, Sixi; Wen, Feiqiu; Gan, Yungen; Song, Jianming; et al. (Frontiers in Pharmacology, 2019)
Background and Objective: Intravenous contrast-enhanced ultrasound (CEUS), using the second-generation ultrasound contrast agent SonoVue®, has been widely used in adults. In 2016, it was approved for pediatric applications by the American Food and Drug Administration (FDA). However, it has not been approved by the Chinese Food and Drug Administration (CFDA). The objective of the study was to evaluate the safety and effectiveness of CEUS in children prospectively at a single center in China. Method: A total of 312 cases of Chinese children were enrolled in clinical trials. Contrast agent was given intravenously with two different doses, including 2.4ml/time and 0.03ml/kg. All CEUS was performed for evaluating adverse effect and the diagnostic accuracy compared with the pathology and enhanced CT. Result: (1) All 312 subjects underwent CEUS successfully. The dose of contrast agent for CEUS was 2.4mL between November 2015 and June 2016, which was modified to 0.03ml/kg between July 2016 and April 2019, according to the recommendation of the FDA. (2) With the two different doses of the contrast agent, the heart rate, respiration rate, oxygen saturation and blood pressure of the participants had no statistically significant difference (P>0.05) before and after administration. The blood pressure had been significantly decreased in participants who received combined anesthetic administration. (3) Following 600 intravenous injections of the CEUS, there were 3 cases of transient rash and 3 cases of hypotension (n=6, 1.92%). The six recovered quickly after receiving intravenous methylprednisolone and epinephrine. (4) Most of the studies were performed for evaluating renal microcirculation and assisting renal biopsy (192/312[61.5%]), which together had a 98.9% effectiveness in the identification of pathology in the specimens. Some studies were conducted to identify a mass in the liver, retroperitoneum, abdominal cavity, kidneys, testicles, thyroid and so on (99/312 [31.4%]), which had a 97.6% accuracy. The other studies were conducted to identify trauma, vascular malformation, infection, hemorrhage and so on (21/312 [6.73%]), which had a similar accuracy to enhanced CT. Conclusion: The adverse effects of CEUS in children are similar to that in adults. The results indicate that it is safe to use SonoVue® for CEUS in paediatric patients.